(untitled) (Experimental biology, 2024)
Kazakhstan became one of the few cohorts of countries that were able to produce its one vaccine against the COVID-19 virus. This fact showed the way of new development paths in the biotechnological direction, especially, since the current situation in the world. Kazakhstan’s location allows its biotechnological development to attract not only academic but also investment interests to make everything possible for producing not only vaccines against the SARS-COV2 virus but also to make biotechnological oriented drug development and antiviral drug production. Also, this article gives the generalized view on current clinical success in combating COVID-19 using novice approaches in biotechnological advancement like humanized IgG ‘Xenomice’ technology in hybridoma technology - REG N10987, produced from transgenic mice and SARS-CoV-2-infected patients [1-3]as well as in human recombinant IgG derived from monoclonal B-cells via Phage display- CT-P59 scFv phage display library generated from cells of a convalescent SARS patient [4]. Along with ‘classical monoclonal IgG LY-CoV555, human Antibody gene cloning of B cells from a COVID-19 patient [5,30]. All these three ‘antivirals’ are already used and approved by the FDA (U.S. Food and Drug Administration) clinically and demonstrate trustworthy therapeutic effects. The biggest upper hand of these approaches is that they can be used not only against the COVID-19 virus but also against various receptor-dependent disorders like lupus or some types of cancer and/or malignant tumors. Last three decades, two main approaches or methods became headliners in research and clinical implementation Hybridoma (B-cell-fusion with ‘immortal’ myeloma cells), and recombination technologies – bound with phage display technologies.